Using cluster analysis to assess some livestock problems in Iraq - Hisham Faroun Abdel Latif; Mortada Mansour Abdullah (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
Due to the occurrence of many changes on the reality of livestock in Iraq and as a result of attempts Avenue infinite numbers of livestock in the past two decades, which led to different data numbers of livestock, which is one of the most important obstacles to the development of a development strategy for the livestock sector in Iraq, which relies basically the preparation of wealth and classes and levels of production. as the most recent year available with data on livestock is the year 2001, in which the agricultural census destruction was and which was implemented by the Ministry of planning / Central Bureau of Statistics, since the conditions and the composition of livestock and livestock products, quality and preparation may differed by virtue of time and extraordinary conditions experienced in Iraq so the recent data on this wealth base building has become a national necessity according to all substantive and developmental standards. Due to the growing importance of livestock and its role as one of the main channels in providing food security requirements, so hence the importance of research in a stand on the most important problems of the Iraqi provinces for livestock has been used style cluster analysis as one of the methods of multivariate analysis and in the classification of the provinces to groups they belong to and build a foundation for the separation of these aggregates in accordance with the most important factors affecting livestock in Iraq. Has beenrelying on the bag SPSS 22.0 statisticalextraction result.